Le fratture-lussazioni della Lisfranc - Di Bisceglie, F.; Mugnaini, M.; Bardelli, M. (Lo Scalpello - Journal, 2018)
LISFRANC FRACTURE-DISLOCATIONS Lisfranc fracture-dislocations are an uncommon injury involving the tarsometatarsal joint and represent a broad spectrum of injuries, which can be purely ligamentous or may involve the osseous and articular structures. Lisfranc injuries are often misdiagnosed and mismanaged; if they are not detected at an early stage and appropriately treated, they can cause long-term disability and will lead to midfoot arthritis. This article outlines the anatomy, epidemiology, classification, investigation and current evidence on treatment of this injury.